Settlement of Contract Defaults Istishna’ on Convection Services Perspective Fatwa DSN-MUI No.06/DSN-MUI /IV/2000 in North Aceh Regency - Nuratun Hadania; Fatimah Zahara (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Along with the times, the convection business in North Aceh Regency has also experienced rapid development. The demand for convection services, especially in clothing manufacturing, is increasing along with the development of the local fashion industry. However, with the rapid development of business, the problem of default of Istishna’s contract is also increasingly frequent. Efforts to resolve problems applied by convection due to defaults that arise in Istishna’ contracts are important to maintain buyer trust and maintain the reputation of the convection business. In addition, the settlement must be in accordance with religious values and applicable law. Based on this, the settlement of defaults that occur must refer to the fatwa from the National Sharia Council (DSN) of the Indonesian Ulema Council (MUI) NO. 06 / DSN-MUI / IV / 2000 concerning the sale and purchase of Istishna’. This study aims to determine the forms of Default of Istishna contract that occur in convection services in North Aceh Regency and to determine the Default Settlement of Istishna contract applied to Convection Services in North Aceh Regency according to the perspective of fatwa DSN-MUI No.06 / DSN-MUI / IV / 2000. The research method used is a qualitative method with a case study approach and uses descriptive analysis. This study concludes that the chosen default resolution prioritizes deliberation as a way to find appropriate and fair solutions. Negotiated or familial dispute resolution between the buyer and the convection party is also highly recommended in Islam and is in accordance with the fatwa DSN-MUI No.06 / DSN-MUI / IV / 2000 which regulates the sale and purchase of Istishna’.